Sense of belonging and job satisfaction in workers of a commercial telecommunications company in Metropolitan Lima - Pérez Yucra, Karina Veronica (2019)
Objective: to determine the relationship that exists between sense of belonging and job satisfaction in the workers of a commercial telecommunications company in metropolitan Lima. Methodology: the instruments used were the Scale of Sense of Belonging of Herrera (2012) that went through content validity (criteria of judges) and the Scale of Labor Satisfaction of Palma (2005), depending on both variables the type of correlational study, of non-experimental and cross-sectional design, with a sample of 202 workers. Results: there is a positive and highly significant relationship between sense of belonging and job satisfaction (r =, 704 **, p = 0.00). In the same way, it resulted in the dimensions of commitment, identification and motivation. Conclusion: a high level of sense of belonging, and its dimensions are related in turn to a high level of job satisfaction in the workers of the commercial company of the telecommunications sector.